Comparative analysis of synthetic indicators of poverty, human development, competitiveness and living standards among departments in 2017 - Quispe Llanos, Renán (2018)
The present investigation has tried to organize to analyze and present the most relevant synthetic indicators that allow to analyze in an integral and complementary way, the demographic, social and economic conditions of the departments. For this reason we have chosen indicators of: Poverty, Human Development, Competitiveness, incorporating to close the circle, an index of living standards, which concentrate a lot of information. In fact, the percentage of poor people according to monetary poverty quantifies the segment of the population whose expenses do not reach a minimum consumption basket. Human development is an indicator of the entire population related to education, health and income conditions. In the economic field, the competitiveness index synthesizes the institutionality, infrastructure, health, education, innovation, environment, sector evolution and economic performance that is presented in the population of the department. Based on a set of demographic, social and economic indicators, an indicator has been developed that summarizes the conditions and quality of life of the Peruvian population. In order to carry out the relational study between the indicators; for each one of them its methodology has been revised in order to know the nature and specify what each indicator measures. It is important to mention that the research contributions are referred to the application of factor analysis and the main components as an instrument for multivariate analysis as a previous step to obtain the standard of living standard. In particular, the detailed process is presented to obtain the synthetic indicator of the standard of living of aspects related to education. Finally, a comparison of the different indices by subject is presented at the de-partmental level, which facilitates the analysis of living standards between departments according to theme.